A review of buyer-supplier relationship typologies: progress, problems, and future directions. Issue 2 (2nd March 2015) - Tangpong, Chanchai; Michalisin, Michael D.; Traub, Rodney D; Melcher, Arlyn J.
Abstract : Purpose: – The purpose of this study is to review the existing typologies of buyer-supplier relationships (BSRs) in the literature, to critically assess their dimensions and underlying assumptions, and to propose a more complete BSR typology and future directions for BSR typology research. Design/methodology/approach: – This study takes a conceptual approach in highlighting the limitations of existing BSR typologies and synthesizing their key typology-defining variables when proposing an alternative BSR typology. Findings: – The proposed BSR typology is based on alternative behavioral assumptions: bounded rationality and choice-determinism, and uses relationalism, supplier dependence and buyer dependence as the typology-defining variables. This BSR typology captures four prominent BSR types in the extant literature (i.e. market/discrete relationship, captive-buyer/supplier-dominant relationship, captive-supplier/buyer-dominant relationship and strategic/bilateral partnership) and four new BSR types developed in this study (i.e. supplier-led collaboration, buyer-led collaboration, competitive/win–lose partnership, and free will/voluntary collaboration). Research limitations/implications: – The performance implications of the new BSR types have yet to be empirically tested; however, empirical approaches for future research are discussed. Originality/value: – As BSR typology research has been conducted over the years, a thorough review and systematic assessment of the extant research in terms of fundamental assumptions, typology-defining variables, overall progress and limitations becomes an important reflective task in guiding future research efforts toward the collective advancement in this line of inquiry. Departing from the existing literature, this study also uses more realistic BSR assumptions and a more complete set of typology-defining variables in developing an alternative BSR typology, arguably more complete and more theoretically sound than the previous BSR typologies in the literature.